ANÁLISE ECONOMÉTRICA DO PREÇO EXTERNO DO COMPENSADO BRASILEIRO - Almeida, Alexandre Nascimento; Ângelo, Humberto; da Silva, João Carlos Garzel Leodoro (Floresta, 2012)
Esta pesquisa teve o objetivo de avaliar a carga de trabalho físico em atividades de implantação florestal em áreas declivosas no sul do Espírito Santo e propor uma reorganização ergonômica para melhoria dos níveis de saúde, bem-estar e satisfação dos trabalhadores. A carga de trabalho físico foi avaliada por intermédio do levantamento da frequência cardíaca, com o uso de monitores de frequência cardíaca nas atividades de construção de cercas, roçada manual, capina química, marcação de covas, coroamento, coveamento manual, enchimento de covas, adubação pré-plantio e plantio. A maior exigência física no trabalho foi verificada na atividade de coveamento manual (125 bpm), sendo esta classificada como moderadamente pesada. A menor exigência física no trabalho foi observada na atividade de adubação pré-plantio, com frequência cardíaca média de 87 bpm, sendo classificada como atividade leve. Foram verificadas diferenças significativas entre as atividades de implantação (médias da carga cardiovascular) pelo teste de Scott-Knott ao nível de 5%, e a necessidade de reorganizar o ambiente de trabalho com inserção de pausas orientadas. Palavras-chave: Ergonomia florestal; frequência cardíaca; plantio florestal; fisiologia do trabalho florestal. Abstract Analysis of the load of physical work in activities of forest implementation insteepareas.This research had the objective to evaluate the load of physical work in activities of forest implementation in steep areas in the south of the Espírito Santo, Brazil and to propose an ergonomic reorganization for improvement of the levels of health, well-being and satisfaction of the workers. The load of physical work was evaluated by the survey of the cardiac frequency with the use of monitors of cardiac frequency in the activities of construction of fencing, manual mowing, weeding chemical, marking of graves, weeding, manual pit, filling of pits, adubation pre-planting and planting. The biggest physical requirement in the work was verified in the activity of manual pit (125 bpm), being classified as moderately heavy activity. The lower physical demands at work were observed in adubation pre-planting, frequently average cardiopath of 87 bpm, being classified as light activity. Significant differences had been verified enter the averages of the cardiovascular load and necessity to reorganize the environment of work with insertion of target pauses. <span style="font-size: 9.0pt; line-height: 115%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">Keywords<span style="font-size: 9.0pt; line-height: 115%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">: Forestry ergonomics; cardiac frequency; forestry activities; physiology of forest work.